Evaluasi Efektivitas Strategi 5S dalam Meningkatkan K3 di Lingkungan Kerja: Studi Kasus pada PT Manakarra Unggul Lestari - Albertus Daru Dewantoro; Prahesti Jihan Permatasari (Universitas Katolik Darma Cendika, 2024)
This study focuses on improving occupational safety and health (OSH) at PT Manakarra Unggul Lestari, a company engaged in palm oil plantation and processing, through the implementation of the 5S method. The analysis primarily examines the Shitsuke (Discipline) aspect, which was found to have the lowest score with an average of 3.092. The objective of this research is to enhance OSH standards within the company by implementing clear steps in Seiri, Seiton, Seiso, Seiketsu, and Shitsuke, supported by Safety measures. Observations were conducted before and after implementation using the 5S and Safety Checklist developed by Todd MacAdam. The results indicate a positive impact of 5S and Safety activities on improving OSH standards, reflected in increased employee discipline and significant changes. Fishbone analysis was also employed to identify key issues within the company, enabling more targeted improvement efforts. This study makes a significant contribution to enhancing OSH in palm oil plantation and processing environments, concluding that the implementation of 5S and Safety can foster a safer work culture and improve employee well-being, aligning with higher OSH standards.